Quantitative evaluation of leukocyte and immunoglobulin production in women undergoing treatment for depression (Research, Society and Development, 2020)
Objective: to verify possible changes in immune system cells (leukogram) and immunoglobulins in women with depression. Methodology: this is an observational, cross-sectional and analytical study conducted with 50 women (with depression n=25; no depression n=25) living in the Araguaia Valley region, Brazil. The women were investigated by collecting a peripheral blood sample, and the concentrations of leukocytes were determined by counting cells by flow cytometry and immunoglobulin concentrations by immunoturbidimetry. The data obtained were analyzed by the Kruskal-Wallis and DUNN tests. This study was approved by an Ethics and Research Committee (CAAE: 34568014.8.0000.5587). Results: the sample consisted of women with a mean age of 37±10,59 years, white/brown and single. Non-smoking women who did not have a habit of consuming alcoholic beverages prevailed. Depression was present among 50% of the sample. Regarding the evaluation of leukogram between the groups (with depression and without depression), a significant difference was observed in the serum value of basophils and the total concentrations of Immunoglobulins did not present significant differences between the groups. Conclusion: in this study, depression did not interfere in the concentration of leukocytic cells or in the production of immunoglobulins, and may be related to the long-term use of psychiatric drugs, because they have immunomodulatory properties, highlighting the importance of performing a treatment and follow-up for Depression.